Communication between children and carers during mealtimes. Issue 4 (5th September 2012) - Harding, Celia; Wade, Candace; Harrison, Kirsty
<x xml:space="preserve">Abstract</x> Mealtimes are identified as an important learning environment where socialisation and language development takes place. Caregivers can facilitate the structure of a child's learning in the mealtime setting. The aim of this study was to gain an understanding about the nature of communication in a normal population during mealtimes. This is important to help understanding about the nature of communication and interaction in children with disabilities during mealtimes. Participants were six typically developing preschool children aged from 8 months to 3;05 years. Caregivers of the children supported their child having a typical meal at home. Each mother–child dyad was video‐recorded by the researchers during a typical meal for up to 30 minutes. Each recording was transcribed by the researchers, and specific communicative features were counted and coded; caregiver comments about appropriate mealtime behaviour, child verbal and nonverbal initiation, caregiver questions and comments about meal enjoyment, caregiver praise of child, and caregiver repetition to coax feeding. A caregiver questionnaire was also completed to obtain information about the child's feeding, any early history of feeding difficulties and typical mealtime routine. The results indicated that the most considerable difference were between the dyads who had reported early feeding difficulties and those who had not reported any. Carers who supported children who had a history of early feeding difficulties used more language to manage and guide the child's behaviour during the mealtime. Caregivers who reported early feeding difficulties appeared to be more concerned with how their child was presenting at the meal (i.e., appropriate behaviour and meal enjoyment). This information has important implications for supporting children with complex needs during mealtimes.